2020
DOI: 10.23736/s1121-421x.19.02577-7
|View full text |Cite
|
Sign up to set email alerts
|

The gut and the inflammatory bowel diseases inside-out: extra-intestinal manifestations

Abstract: An increasing deal of attention is being conveyed on the extra-intestinal manifestations of inflammatory bowel diseases (IBD). We compiled the present review in an attempt to upgrade the accuracy of the classification of such polymorphic entities. We focused on three patterns. First, the conventional extra-intestinal manifestations localized to bone and joints, to the eye, to the biliary tree and to the skin. Second, the so-called IBD-like syndromes accompanied by bone marrow-derived anomalies of innate or acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…While UC affects the rectum and a variable extent of the colon, CD can involve any location of the gastrointestinal (GI) tract, from the oral cavity to the anus. Furthermore, up to 36% of patients with IBD may have extra-intestinal manifestations (EIM) [3][4][5] which can affect almost any organ of the body (eyes, joints, liver, pancreas, skin, blood, and mouth) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…While UC affects the rectum and a variable extent of the colon, CD can involve any location of the gastrointestinal (GI) tract, from the oral cavity to the anus. Furthermore, up to 36% of patients with IBD may have extra-intestinal manifestations (EIM) [3][4][5] which can affect almost any organ of the body (eyes, joints, liver, pancreas, skin, blood, and mouth) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 While the disease is predominantly described as a gastrointestinal disease, symptoms involving other organ systems are increasingly recognized. 3,4 In the past decade, studies conducted in both animals and human models have suggested that several genetic factors are involved in the pathogenesis of IBD. [5][6][7][8][9][10] Animal studies have argued for an immune mediated role for IBD.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Although it is reported that the pathogenesis of IBD originates from a dysregulated interaction between genetic and environmental factors, the precise etiology is still unknown [2,3]. Patients may also present extra-intestinal manifestations, such as arthritis, erythema nodosum, uveitis, or primary sclerosing cholangitis [4]. It is estimated that 1.5 million Americans and 2.2 million people in Europe are affected by IBD, and several studies have identified an increase in incidence, particularly in newly industrialized countries [5,6].…”
Section: Introductionmentioning
confidence: 99%